Multicentre randomised controlled trial comparing standard and high resolution optical technologies in colorectal cancer screening. Issue 3 (26th February 2019) - Di Caro, Simona; Fini, Lucia; Vega, Roser; Fragkos, Konstantinos C; Dolwani, Sunil; Green, John; Smith, Lesley-Ann; Beckett, Conrad; Cameron, Ewen; Banks, Matthew
Abstract : Background and objectives: The UK bowel cancer screening programme (BCSP) has been established for the early detection of colorectal cancer offering colonoscopy to patients screened positive by faecal occult blood tests. In this multisite, prospective, randomised controlled trial, we aimed to compare the performance of Standard Definition Olympus Lucera (SD-OL) with Scope Guide and the High Definition Pentax HiLine (HD-PHL). Patients and methods: Subjects undergoing a colonoscopy as part of the UK National BCSP at four UK sites were randomised to an endoscopy list run using either SD-OL or HD-PHL. Primary endpoints were polyp and adenoma detection rate (PDR and ADR, respectively) as well as polyp size, morphology and histology characteristics. Results: 262 subjects (168 males, mean age 66.3±4.3 years) were colonoscoped (133 patients with HD-PHL while 129 with SD-OL). PDR and ADR were comparable within the two optical systems. The HD-PHL group resulted in a PDR 55.6% and ADR 43.6%; the SD-OL group had PDR 56.6% and ADR 45.7%. HD-PHL was significantly superior to SD-OL in detection of flat adenomas (18.6% vs 5.2%, p<0.001), but not detection of pedunculated or sessile polyps. Patient comfort, use of sedation and endoscopist perception of procedural difficulty resulted similar despite the use of Scope Guide with SD-OL. Conclusion: PDR and ADR were not significantly different between devices. The high-resolution colonoscopy system HD-PHL may improve polyp detection as compared with standard resolution technology in detecting flat adenomas. This advantage may have clinically significant implications for missed lesion rates and post-colonoscopy interval colorectal cancer rates.